Efficacy of Pseudomonas aeruginosa and Trichoderma asperellum in promoting plant growth and suppression of Ganoderma boninense disease infestations in oil palm - Ms, Muniroh; Syd Ali, Nusaibah; Vadamalai, Ganesan (Academic Press, 2025)
The most common disease affecting Malaysian palms is basal stem rot (BSR), which is caused by Ganoderma species. Pre-inoculation of oil palm seedlings with Trichoderma asperellum and/or Pseudomonas aeruginosa was conducted to study their effects on the vegetative development and BSR disease suppression. A 32-week nursery trial was conducted on four-month-old oil palm seedlings (D × P) utilizing the dip, place, and drench (DPD) artificial inoculation technique. Disease severity (DS) was determined by root symptoms in conjunction with the influence of vegetative growth. In addition, root samples were collected at eight months after inoculation (MAI) and analyzed using GC-MS to investigate the expression of metabolites generated as a defensive response to G. boninense infection. Using BCAs helped oil palm seedlings grow better than those that weren't treated. The single application of T. asperellum and the combination of P. aeruginosa and T. asperellum had the greatest impact on the growth of the oil palm seedling's plant height (143.0 cm ± 0.02) and (140.45 cm ± 0.02), respectively. Seedlings infected with G. boninense and treated with a mixture of BCAs had the highest top and root weight and the lowest DS (50 %), compared to seedlings infected with G. boninense (positive control) (83.3 %). Furthermore, GC-MS analysis revealed that treatment with BCAs produced plant secondary metabolites that may be involved in antimicrobial and plant defense systems, and as plant growth promoters.